128k views
3 votes
Solve for x assuming the expression is set to 0:

Solve for x assuming the expression is set to 0:-example-1
User UmmaGumma
by
5.3k points

1 Answer

3 votes

Answer

Step-by-step explanation

Given:


-x^2-2x-3=0

Then, we can multiply the whole expression times -1:


x^2+2x+3=0

Next, we can find the solution for x using the General Quadratic Formula:


x_(1,2)=(-b\pm√(b^2-4ac))/(2a)

where a, b and c are the coefficients of the quadratic equation in the form ax² + bx + c = 0. Thus, considering that in our case a = 1, b = 2 and c = 3:


x_(1,2)=(2\pm√(2^2-4(1)(3)))/(2(1))
x_(1,2)=(2\pm√(4-12))/(2)
x_(1,2)=(2\pm√(-8))/(2)

Finally, calculating the two solutions:


User Maksym Rudenko
by
5.2k points